Uji Pupuk Kompos Akibat Penambahan Sludge Minuman Berkarbonasi terhadap Hasil Sawi Hijau (Brassica juncea L.) dan Beberapa Perubahan Sifat Kimia Tanah - Devin Ronaldo Naidu; A. A. Nyoman Supadma; I Dewa Made Arthagama (Fakultas Pertanian, Universitas Udayana, 2021)
The purpose of this study was to determine the effect of giving additional doses of compost fertilizer with carbonated beverage sludge and sludge on the chemical properties and growth yield of mustard greens (Brassica juncea L.). This research was carried out from March 2021 to May 2021 and used a Randomized Block Design (RBD) consisting of 8 treatments, including control which was repeated three times with 24 experimental pots. The treatment tried was P0 = no fertilizer (control). P1 = 5 tons of compost/ha-1 (11.25 grams of compost/pot-1), P2 = 10 tons of compost/ha-1 (22.5 grams of compost/pot-1), P3 = 15 tons of compost/ha- 1 (34 gr compost/pot-1), P4 = 20 tons compost/ha-1 (45 gr compost/pot-1), P5 = 5 tons sludge/ha-1 (11.25 sludge/pot-1), P6 = 10 tons of sludge/ha-1 (22.5 gr sludge/pot-1), P7 = 15 tons of sludge/ha-1 (34 gr sludge/pot-1). The parameters observed in this study were divided into two observations, observing soil chemical properties, including pH, N-total, P-available, K-available, Electrical Conductivity (EC), C-organic, Cation Exchange Capacity (CEC), and Base Saturation. Plant parameters are consisting of plant height, number of leaves, fresh weight, plant dry weight. The results of statistical analysis showed the fertilizer dose had a very significant effect (P>0.01) on K-available, P-available, BS and had a significant effect (P <0.05) on pH and EC, but had no significant effect (P> 0.05) on N- total, C-organic, CEC, plant height, number of leaves, fresh weight, and plant dry weight. P7 treatment showed that the best improvement in plant parameters such as plant height which increased by 20%, and fresh weight of 45% from the control treatment. The chemical properties of available P-available increased by 25%, available K-available increased by 22%, and BS increased by 10% from the control.